STUDI EKSPERIMENTAL PENGARUH TEGANGAN TEKAN SELAMA PROSES PRODUKSI TERHADAP KUAT TEKAN DRY CONCRETE - M. Mirza Abdillah Pratama; Vemi Widoanindyawati; Han Ay Lie; Purwanto Purwanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Dry concrete is basically a cementitious material, consisting of aggregates imbedded in a cement matrix that function as the binding agent. The water cement factor during this production is customary kept low, since from the economic point of view, speed in production is favored. A low water-cement-factor will result in a faster unmolding of elements. As a consequence, the probability of the hydration process is not at optimum. A technique of optimizing the hydration process is to apply a compression stress to the dry concretes, during the hydration stage. This stress is aimed to reduce the air voids in the mixture and to enable the entrapped water within the mortar to optimize the reaction with the cement. The application of compression stress is not only freed the entrapped water, but also creates a more dense material so it will provides a better performance of the dry concrete. This study uses 2 types of mix design with a water-cement ratio of 0.4 and 9 types of compressive stress variations during the production process from 0 MPa to 40 MPa. The experimental test showed that the compressive stress during the production process affect the compressive strength of dry concrete. The greater compressive stress given during the production process increase the compressive strength of the dry concrete. This increase occurred gradually until it reaches the optimum compressive stress, which is 35 MPa. The rate of increase in compressive strength and the optimum compressive stress on both the mix design is in the same point, it is due to both the mix design using the same water-cement ratio.